Analysing the effectiveness of T-shirt business start-up branding through online platform at Malaysian T-shirt business community - saleh, hasan (International Journal of Human and Technology Interaction (IJHaTI), 2022)
Building a brand is a core business activity, just as important as leasing office space, recruiting the right people or developing your product or service. To provide all this involve lot of money. Anyone who does sales and owned the brand knows that this is not easy. New business owners typically don’t have lot of money to invest in business. Therefore, the purpose of this study is to investigate how to be the owner of the product in apparel industry with start-up business t-shirt branding through online platforms with low cost and risk to the acceptance of the customers at the business community. From this study its can be conclude that there has strong relationship between online platforms that influences the effectiveness of start-up T-shirt business branding.